Lifestyle of people aged 60+ who report for preventive examination - Szamocka, Małgorzata; Ameryk, Monika Anna; Świątkowski, Maciej (Journal of Education, Health and Sport, 2017)
Lifestyle, with such components as diet, food quality, nutritional status and physical activity in different age groups, including people aged 60+, is a popular research field. Between 1989 and 2014, the number of elderly people in Poland increased by nearly 3 million. Lifestyle, formed from the childhood, is a very important factor affecting a person’s heath status and quality of life, particularly in the elderly. The aim of the study was to assess the lifestyle of people aged 60+ who reported for a screening examination for the early detection of colorectal cancer. The group consisted of 100 people aged 60+ who underwent a screening examination for the early detection of colorectal cancer conducted at the Clinic of Gastroenterology and Nutrition Disorders, the Jan Biziel University Hospital no. 2 in Bydgoszcz, Poland. Every participant filled two surveys, one concerning their current and past lifestyle and the other assessing their eligibility for colonoscopy screening. Every participant underwent a physical examination and anamnesis, during which basic anthropometric parameters, including body weight (kg) and height (cm), were assessed, followed by colonoscopy screening. Statistical analysis was conducted using STATISTICA PL 13 computer software from StatSoft and the results were considered as statistically significant at p<0.05. The mean overall value of the participants’ BMI was 27.8 ± 6.5 kg/m2, which indicated overweight in accordance with the WHO criteria. By categorizing the BMI measurements, it was shown that women were twice more likely to have a correct body weight compared to men (33% vs. 15%) and had a lower incidence of obesity (20% vs. 26%). Daily physical activity was practiced by 13% of the participants, while sedentary lifestyle was reported by nearly one-third of them. 70% of the surveyed group spent 2 to 3 hours per day watching TV or using a computer. Nutrition analysis demonstrated that almost 60% of the patients implemented modifications to their diet. Colonoscopy screening conducted in people aged 60+ revealed the presence of colorectal abnormalities in 44% of the participants, including 6 cases of colorectal cancer. The results of the study indicated cases of inappropriate diet, food quality and nutritional status, as well as other errors in health-related behavior. The identification of the discovered problems should encourage the Polish health care institutions to implement health promotion programs targeting people from their childhood, as well as carefully selected prevention programs for people aged 50 to 70 years.